Toward REBCO 20 T+ Dipoles for Accelerators - van Nugteren, Jeroen; Kirby, Glyn; Murtomaki, Jaakko; DeRijk, Gijs; Rossi, Lucio; Stenvall, Antti (IEEE transactions on applied superconductivity, 2018)
ReBCO high temperature superconducting (HTS) coated conductor tapes are a promising candidate for pushing the magnetic fields in accelerator magnets well beyond 20 T. They are capable of very high current densities in intense applied magnetic field, have a very high thermal stability, can withstand high transverse pressures and allow operation in 20-30 K helium gas flow, potentially reducing operating cost significantly. During the EuCARD2 program, significant developments have been made in terms of coil design, manufacturing, and testing. Now that EuCARD2 has come to an end, CERN and collaborators are initiating a new program to continue the development of HTS accelerator magnets. This paper presents our initial thoughts on the conceptual design of a 20 T+ accelerator magnet, using the results and technologies from EuCARD2 combined with some new ideas. The paper discusses the options available for the cross-sectional layout, the use of a hybrid configurations, including Aligned Block, the design of the coil-ends and dual aperture configurations. Also, discussed is the quench protection of the magnets. Due to the high thermal stability of the conductor and high energy densities, it will be required to explore an entirely a new approach.